A proposed methodology of bringing past life in digital cultural heritage through crowd simulation: a case study in George Town, Malaysia - Lim, C. K. (Tanjong Malim, 2020)
A proposed methodology of bringing past life in digital cultural heritage through crowd simulation: a case study in George Town, Malaysia by Lim, C. K.